THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENTS' SELF-CONCEPT AND METACOGNITIVE ABILITY ON EXCRETION SYSTEM - Najihah Fakhirah Siregar; Ely Djulia (Universitas Negeri Medan, 2021)
Science education aims to enable teachers to teach problem-solving in the teaching and learning process. Students should have at least two competencies to achieve learning objectives, including metacognitive abilities and the ability to recognize their potential, interests, talents. The ability to recognize potential, interests, and talents are related to self-concept. One alternative learning model that can develop a positive self-concept and train students' metacognitive abilities is the problem-based learning model. The learning process on the excretory system material demands a process of discovery and problem solving that trains students' metacognitive abilities. This study aims to determine the effect of the Problem Based Learning model on students' self-concept and metacognitive abilities. The research sample was two classes obtained based on the purposive sampling technique. The research design used is the Pretest-Postest Nonequivalent Control Group Design. The research data was obtained from self-concept questionnaires and students' metacognitive abilities. The results showed that the average value of self-concept and metacognitive abilities of students taught using the PBL model was more significant than the class taught using the DL model. The results of hypothesis testing and effect size also show that the PBL model significantly affects students' self-concept and metacognitive abilities with scores of 1.9 (high) and 2.4 (high).